Quantification of ribonucleotide reductase expression in wild-type and hydroxyurea-resistant cell lines employing in situ reverse transcriptase polymerase chain reaction and a computerized image analysis system - Wadler, S; Zhang, H; Cammer, M; Hu, X P (Analytical biochemistry, 1999)
Ribonucleotide reductase (RR) is the enzyme responsible for converting nucleoside diphosphates to deoxynucleoside diphosphates, ensuring a balanced supply of deoxyribonucleotides for DNA synthesis. Expression of RR is tightly regulated, but it is affected by exogenous agents, such as hydroxyurea (HU), which inactivates the tyrosyl free radical on the small subunit of RR, R2. We have previously employed in situ reverse transcriptase (RT)-PCR to estimate expression of R2 in wild-type and HU-resistant human colon carcinoma cell lines and to correlate altered expression of R2 with changes in cell size and morphology. The current studies were undertaken to render this methodology more quantitative. Both wild-type and resistant cells were grown on partitioned glass slides and analyzed with in situ RT-PCR. Because both wild-type and resistant cells were analyzed under a single cover slip, protease digestion, reverse transcription, PCR, and color development were all performed under identical conditions. Images were analyzed with NIH Image 1.59 software. There was a highly significant correlation between expression of R2 and cell size for both sensitive and resistant cells (P = 0.0001, for both). When cell size was compared either with expression of R2 or cell shape, however, these correlated only in wild-type cells (P = 0.001 and 0.0001, respectively). These data demonstrate that normal cell growth in the unperturbed wild-type cell line was closely linked to expression of R2, whereas in the resistant variants which overexpress R2, these correlations were absent, suggesting that HU resistance is related to loss of linkage between R2 expression and cell growth and confirming previous data relating overexpression of R2 with multiple other changes in the cell growth repertoire. Thus, we have demonstrated for the first time a quantitative application of in situ RT-PCR.